PERANCANGAN DAN PENGEMBANGAN TAS BACKPACK ERGONOMIS DAN MULTIFUNGSI - Nataya Charoonsri Rizani; Agie Satria (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Backpack is one of the most attractive bag because of its excellence in the load management.Based on customer’s need identification, there were several primary dan secondary needs. Backpackdesign then was following the rules of product design with attention to ergonomic and financialaspects. Products were designed and developed, made a prototype and tested over a period of timeon the user. Results feedback during implementation include aspects of shapes, sizes, features anddesign.